Controlling Victimization in Schools: Effective Discipline and Control Strategies in a County in Ohio, 1994 - Lab, Steven P. ([Verlag nicht ermittelbar], 1998)
The purpose of this study was to gather evidence on the relationship between discipline and the control of victimization in schools and to investigate the effectiveness of humanistic versus coercive disciplinary measures. Survey data were obtained from students, teachers, and principals in each of the 44 junior and senior high schools in a county in Ohio that agreed to participate in the study. The data represent roughly a six-month time frame. Students in grades 7 through 12 were anonymously surveyed in February 1994. The Student Survey (Part 1) was randomly distributed to approximately half of the students in all classrooms in each school. The other half of the students received a different survey that focused on drug use among students (not available with this collection). The teacher (Part 2) and principal (Part 3) surveys were completed at the same time as the student survey. The principal survey included both closed-ended and open-ended questions, while all questions on the student and teacher surveys were closed-ended, with a finite set of answers from which to choose. The three questionnaires were designed to gather respondent demographics, perceptions about school discipline and control, information about weapons and gangs in the school, and perceptions about school crime, including personal victimization and responses to victimization. All three surveys asked whether the school had a student court and, if so, what sanctions could be imposed by the student court for various forms of student misconduct. The student survey and teacher surveys also asked about the availability at school of various controlled drugs. The student survey elicited information about the student's fear of crime in the school and on the way to and from school, avoidance behaviors, and possession of weapons for protection. Data were also obtained from the principals on each school's suspension/expulsion rate, the number and type of security guards and/or devices used within the school, and other school safety measures. In addition to the surveys, census data were acquired for a one-quarter-mile radius around each participating school's campus, providing population demographics, educational attainment, employment status, marital status, income levels, and area housing information. Also, arrest statistics for six separate crimes (personal crime, property crime, simple assault, disorderly conduct, drug/alcohol offenses, and weapons offenses) for the reporting district in which each school was located were obtained from local police departments. Finally, the quality of the immediate neighborhood was assessed by means of a "windshield" survey in which the researchers conducted a visual inventory of various neighborhood characteristics: type and quality of housing in the area, types of businesses, presence of graffiti and gang graffiti, number of abandoned cars, and the number and perceived age of pedestrians and people loitering in the area. These contextual data are also contained in Part 3.